Ulam stability of Volterra integral equation on a generalized metric space - CIPLEA, Sorina Anamaria; LUNGU, Nicolaie (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The aim of this paper is to give some Ulam-Hyers stability results for Volterra integral equations on a generalized metric space. In this case we consider the Volterra integral equation in the Krasnoselski-Krein and Naguno-Perron-Van Kampen conditions. Here we present only Ulam-Hyers stability for the Volterra integral equation. Mathematics Subject Classification (2010): 45G10, 45M10, 47H10, 47J20.